Chalcogen complexes of anionic N-heterocyclic carbenes. Issue 38 (12th August 2020) - Ho, Luong Phong; Körner, Lukas; Bannenberg, Thomas; Tamm, Matthias
Abstract : Chalcogen complexes of anionic N-heterocyclic carbenes were isolated as lithium salts and their protonation and oxidation were studied. Abstract : Several group 16 adducts of the type [(WCA-IDipp)E]Li(solv.) that bear an anionic N-heterocyclic carbene ligand with a weakly coordinating borate moiety (WCA-IDipp, WCA = B(C6 F5 )3, IDipp = 1, 3-bis(2, 6-diisopropylphenyl)imidazolin-2-ylidene, E = O, S, Se, Te) were prepared. This was achieved by deprotonation of the corresponding ketone (IDipp)O or thione (IDipp)S with n -BuLi and subsequent reaction with B(C6 F5 )3 or by direct reaction of [WCA-IDipp]Li(toluene) with elemental Se or Te. The oxygen, sulfur and selenium adducts can be protonated to give derivatives (WCA-IDipp)EH (E = O, S, Se), whereas the oxidation of the sulfur and selenium adducts yielded neutral disulfide and diselenide species (WCA-IDipp)2 E2 (E = S, Se).